Assembly manual for the proteasome regulatory particle: the first draft. (19th January 2010) - Park, Soyeon; Tian, Geng; Roelofs, Jeroen; Finley, Daniel
Abstract : The proteasome is the most complex protease known, with a molecular mass of approx. 3 MDa and 33 distinct subunits. Recent studies reported the discovery of four chaperones that promote the assembly of a 19-subunit subcomplex of the proteasome known as the regulatory particle, or RP. These and other findings define a new and highly unusual macromolecular assembly pathway. The RP mediates substrate selection by the proteasome and injects substrates into the CP (core particle) to be degraded. A heterohexameric ring of ATPases, the Rpt proteins, is critical for RP function. These ATPases abut the CP and their C-terminal tails help to stabilize the RP–CP interface. ATPase heterodimers bound to the chaperone proteins are early intermediates in assembly of the ATPase ring. The four chaperones have the common feature of binding the C-domains of Rpt proteins, apparently a remarkable example of convergent evolution; each chaperone binds a specific Rpt subunit. The C-domains are distinct from the C-terminal tails, but are proximal to them. Some, but probably not all, of the RP chaperones appear to compete with CP for binding of the Rpt proteins, as a result of the proximity of the tails to the C-domain. This competition may underlie the release mechanism for these chaperones. Genetic studies in yeast point to the importance of the interaction between the CP and the Rpt tails in assembly, and a recent biochemical study in mammals suggests that RP assembly takes place on pre-assembled CP. These results do not exclude a parallel CP-independent pathway of assembly. Ongoing work should soon clarify the roles of both the CP and the four chaperones in RP assembly.